HONORIFIC SUBJECTIVE PRONOUNS USED BY MINANGNESE IN KECAMATAN MEDAN AREA - FAHMI FAHMI; ZAINUDDIN ZAINUDDIN; MUHAMMAD NATSIR (LINGUISTICA, 2020)
This study aimed to reveal and explain honorific subjective pronouns used by Minangnese in Kecamatan Medan Area by trying to find out the type most used, the way, and the reason of people in Kecamatan Medan Area to use it. This study used a descriptive qualitative method, this study conducted in Kecamatan Medan Area, there were 32 Minangnese in Kecamatan Medan Area as respondents. In this research, the data collected by using an interview and questionnaire. The findings of this study that Minangnese Subjective Pronouns in Kecamatan Medan Area mostly used were first honorific subject pronouns Ambo/Denai with 93 times chosen, second honorific subject pronouns Menyebut nama orang lain (call a name) with 91 times chosen, and third Personal Subject Pronouns si + nama orang with 120 times chosen. Age, gender, situation, and formality that determined the way of people in Kecamatan Medan Area using honorific subjective pronouns and reason of respondents in Kecamatan Medan Area using Minangnese honorific subjective pronouns were adapting situation and politeness